Students’ Course Grades Analysis “Practical Case” - Hussein Chible (East Asian Journal of Multidisciplinary Research, 2022)
To maintain the benefits and improve the course procedure for the next year, this work is devoted to evaluating my course of computer at the faculty of tourism at the Lebanese University during the academic year 2021–2022. Additionally, we want to mention that this method can be used as a model for any similar course evaluation. According to the results, some variables of grades are normally distributed while others are not normally distributed. The final grade average and partial grade average for each student are different from one another. Final grades were statistically equal for both male and female students. The final grade average for this year and last year is the same. There is a correlation between participation and presence grades and the other grades, except the mid-exam grades. Also, the final grades and all other grades, except the mid-exam grades, are correlated. For the following year, we need to make sure that students attend more lectures to raise their grades. Also, to have an impact on final grades, we need to put more effort into mid-exam preparation.